Mutations in genes encoding condensin complex proteins cause microcephaly through decatenation failure at mitosis - Martin, C. (2016)
Compaction of chromosomes is essential for accurate segregation of the genome during mitosis. In vertebrates, two condensin complexes ensure timely chromosome condensation, sister chromatid disentanglement, and maintenance of mitotic chromosome structure. Here, we report that biallelic mutations in NCAPD2, NCAPH, or NCAPD3, encoding subunits of these complexes, cause microcephaly. In addition, hypomorphic Ncaph2 mice have significantly reduced brain size, with frequent anaphase chromatin bridge formation observed in apical neural progenitors during neurogenesis. Such DNA bridges also arise in condensin-deficient patient cells, where they are the consequence of failed sister chromatid disentanglement during chromosome compaction. This results in chromosome segregation errors, leading to micronucleus formation and increased aneuploidy in daughter cells. These findings establish "condensinopathies" as microcephalic disorders, with decatenation failure as an additional disease mechanism for microcephaly, implicating mitotic chromosome condensation as a key process ensuring mammalian cerebral cortex size.